The development of a new protocol to assess performance measure in sport - Norris, M.; Breen, S.; Anderson, R.; Kenny, I. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to develop a novel protocol to be used in assessing performance outcomes in projectile sports. This study also wanted to establish if variability within a movement pattern (throwing) is detrimental to the outcome of that skill and to assess the validity of curret methods used to measure performance. Single subject analysis was undertaken as 4 Wilson TrainerTM tennis balls were launched using a Tennis CubeTM launcher at a wall 25 times each. Infra-red light gate technique (wall mounted OptojumpTM) in which ball tracking co-ordinates were obtained were compared to traditional movement measure device (3D Motion Analysis CorporationTM) coordinates. Agreement between the 3D landing point X and Y coordinates and the OptojumpTM landing points X and Y coordinates were analysed using the Bland- Altman method.